2020
DOI: 10.1002/lno.11476
|View full text |Cite
|
Sign up to set email alerts
|

Coastal carbon cycle changes following mangrove loss

Abstract: Global mangrove loss is occurring from deforestation and extreme climatic events, but changes to the coastal carbon cycle following mangrove mortality and/or loss are not well understood. In 2015/2016, a massive climate-driven mangrove dieback event occurred over~1000 km of Australian coastline. To assess carbon loss following mortality, carbon fluxes in adjacent living and dead forest areas were compared 8 and 20 months postforest dieback. Dead areas experienced an increase in soil CO 2 efflux by~189%, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
(91 reference statements)
1
16
0
1
Order By: Relevance
“…Degradation of these wetlands could release the C trapped in the soil which could result in relatively higher C emissions (Sharma et al, 2020). A recent study estimated that the ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C year −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60% (Sippo et al, 2020). A report also suggests that the loss of trapped C from the sediments due to degradation is higher than the C stock in the sediments contributed by above-ground vegetation (Kauffman et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Degradation of these wetlands could release the C trapped in the soil which could result in relatively higher C emissions (Sharma et al, 2020). A recent study estimated that the ongoing global carbon losses from historical mangrove deforestation and dieback could be 13.7 ± 9.4 Tg C year −1 , which is eightfold higher than previous estimates and offsets global mangrove carbon burial by ~ 60% (Sippo et al, 2020). A report also suggests that the loss of trapped C from the sediments due to degradation is higher than the C stock in the sediments contributed by above-ground vegetation (Kauffman et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The loss of mangrove habitats due to extreme climatic events has also become more common (Duke et al, 2017;Servino et al, 2018). A recent study reported a massive climate-driven mangrove dieback incident has experienced an increase in soil CO 2 efflux by ~ 189% and a decrease in oceanic dissolved inorganic carbon (DIC) outwelling of ~ 50% comparative to other areas with live mangroves (Sippo et al, 2020). Globally, from 2000 to 2015 mangrove forest destruction has led to a loss of 30-122 Tg C stored in the soil, with >75% of this loss attributed to Indonesia, Malaysia and Myanmar (Sanderman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather patterns in the past few years have caused extensive areas of mangrove tidal wetland vegetation dieback in northern Australia (Addicott et al, 2020; Asbridge et al, 2019; Duke et al, 2017) with the nature of these events being attributed to a low sea level event that was also associated with El Niño conditions (Sippo et al, 2020). Similarly, in the austral summer of 2010/2011, a marine heatwave associated with El Niño resulted in the collapse of ~1300 km 2 of seagrass extent in Shark Bay, Western Australia (Arias‐Ortiz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ekosistem mangrove dengan jenis homogen memiliki jasa ekosistem karbon yang lebih rendah dibandingkan dengan mangrove campuran (Tinh et al, 2020). Namun, mangrove yang terdegradasi akan terancam kehilangan keanekaragaman biota dan jasa ekosistemnya (Carugati et al, 2018;Sippo et al, 2020). Oleh karena itu, penentuan kualitas komunitas mangrove sangat diperlukan untuk menganalisis jasa ekosistem mangrove.…”
Section: Pendahuluanunclassified